Challenges experienced by genetic counselors while they provided counseling about mosaic embryos - Olivia M. Moran, M.Sc; Kayla Flamenbaum, M.S; Diane Myles Reid, M.S; Jeanna M. McCuaig, Ph.D; Riyana Babul-Hirji, M.Sc; David Chitayat, M.D; Maian Roifman, M.D (Elsevier, 2023)
Objective: To survey genetic counselors (GCs) who have counseled about mosaic embryos regarding the challenges they faced in counseling this patient population and assess their need for more resources to support their practice. Design: Self-administered online survey. Setting: Academic university. Study Population: Seventy-eight GCs primarily from the United States and Canada. Intervention(s): Genetic counselors completed a quantitative survey with an embedded qualitative component. Quantitative data were analyzed by descriptive statistics. An inductive thematic analysis was performed on open-text responses. Main Outcome Measure(s): Genetic counselors were asked what clinical activities relating to mosaic embryos they performed. They were then asked to rate how challenging each activity was to perform using a 5-point scale; a rating of 4 or 5 was defined as highly challenging. Open-text questions enabled GCs to describe factors that they felt contributed to these challenges. Result(s): The challenges reported by GCs included the uncertainty of outcomes in offspring after mosaic embryo transfer, limited guidelines available to assist clinicians with counseling about mosaic embryos, and ranking mosaic embryos by suitability for transfer. The contributing factors suggested by participants included limited outcome data, limited GC involvement in pretest counseling for preimplantation genetic testing for aneuploidy (PGT-A), and perceived inconsistency in counseling practices across clinics. Genetic counselors differed in their genetic testing recommendations for pregnancies conceived after mosaic embryo transfer. Amniocentesis and postnatal assessment were recommended by 85% and 49% of GCs, respectively, and 15% recommended chorionic villus sampling and noninvasive prenatal testing. Almost all (92%) reported a need for more resources, such as standardized guidelines, more outcome data, and continuing education on PGT-A and mosaicism. Conclusion(s): This study describes challenges experienced by GCs while they counseled about mosaic embryos. Our findings demonstrate a need for more outcome data on mosaic embryo pregnancies and for evidence-based clinical guidelines. The differing recommendations for prenatal genetic testing among GCs in the study warrant further research into contributing factors. We strongly recommend that pretest counseling, including a discussion regarding mosaicism, is provided to all couples considering PGT-A to reduce counseling challenges and to promote patients' informed decision-making.